Exposure to sublethal concentrations of thiacloprid insecticide modulated the expression of microRNAs in honeybees (Apis mellifera L.) - Tengfei Shi; Xingchuan Jiang; Haiqun Cao; Linsheng Yu (Ecotoxicology and Environmental Safety, 2023)
This study aimed to investigate the sublethal effects of thiacloprid on microRNA (miRNA) expression in honeybees (Apis mellifera L.) and the role of a specific miRNA, ame-miR-283–5p, in thiacloprid resistance. The high-throughput small RNA-sequencing was used to analyze global miRNA expression profile changes in honeybees orally exposed to sublethal concentrations of thiacloprid (20 mg/L and 4 mg/L) for 72 h. Thiacloprid at 20 mg/L had no observed adverse effects. In addition, bees were fed with miRNA mimics or inhibitors to increase or decrease ame-miR-283–5p expression, and its effects on P450 gene expression (CYP9Q2 and CYP9Q3) were examined. Thiacloprid susceptibility was also detected. The results showed that treatment with thiacloprid at 20 mg/L and 4 mg/L induced 11 and five differentially expressed miRNAs (DEMs), respectively. Bioinformatic analysis suggested that the DEMs are mainly involved in the regulation of growth and development, metabolism, nerve conduction, and behavior. ame-miR-283–5p was downregulated by both concentrations, which was validated using quantitative real-time reverse transcription PCR analysis. Enhancing ame-miR-283–5p expression significantly inhibited CYP9Q2 mRNA and protein expression, and increased thiacloprid toxicity, while reducing ame-miR-283–5p expression significantly promoted CYP9Q2 expression, and decreased thiacloprid susceptibility. Our study revealed a novel role of miRNAs in insecticide resistance in honeybees.